European erotic Romance : philhellene Protestantism, renaissance translation and English literary politics - Skretkowicz, Victor; Frost, Matthew; Manchester University Press (Manchester, UK : Manchester University Press, 2018)
European Erotic Romance examines the Renaissance publication and translation of the ancient Greek erotic romances, and English adaptations of the genre by Sir Philip Sidney, Shakespeare and Lady Mary Sidney Wroth. Providing fresh insight into the development of the novel, this study identifies the politicisation of erotic romance by the European philhellene (lovers of all things Greek) Protestant movement. To English translators and authors, the complex plots, well developed moralised characters (particularly female) and rhetorical styles of the ancient novels signify political and social reform. Generous quotation and translations ensure that European Erotic Romance is accessible to a broad spectrum of readers. Its organisation lends itself to use as a course text. It is suitable for use by senior undergraduates and specialists in Renaissance literature, translation, rhetoric and history.
Introduction -- Part One: Greco-Roman Romance in the Renaissance -- 1 The Nature of Erotic Romance -- Greco-Roman Romance of the Second Sophistic and the Renaissance -- Aphthonius, Philostratus, Ecphrasis and Artistic Style -- Characterisation: Theophrastus and Plutarch -- Philhellenism and the Allegorical Politicisation of Erotic Romance -- 2 Longus's Daphnis and Chloe -- The Novel as Ecphrasis -- Amyot, Translation and the Kings of France -- Reading, Education and Translation -- Translating Erotic Romance -- Angel Day, The Shepheards Holidaie and Accession Day, 1587 -- The Shepheards Holidaie, Court Drama, and Court Poets -- Translating Eros: Amyot, Day and Thornley -- George Thornley's Itch -- Angel Day and Dionysophanes' Garden -- The End: Nothing But Shepherds' Games -- Conclusion -- 3 Achilles Tatius's Leukippe and Kleitophon -- Rhetorics of Love -- European Dissemination -- Belleforest's French -- Burton and the English Philhellenes -- Hodges, Erotic Arousal and Sidney's Arcadia -- Translating the Opening -- Europa: An Ecphrasis -- Europa and Apparent Cyclic Form -- Kleitophon and Characterisation -- Kleitophon's Symbolic Dream -- Kleinias on Love, Sex and Marriage -- Kleitophon's Garden -- Pantheia's Dream -- Debate on Erotic Love -- Sexual Predation -- Melite and Thersandros -- The Trial and Conclusion -- Conclusion -- 4 Heliodorus's An Ethiopian Story -- Theagenes and Charikleia -- Charikliea: Royal Foundling -- Renaissance Continental Translations and Philhellene Politics -- Sandford's Historie of Chariclia and Theagenes -- Underdowne's An Aethiopian Historie -- Fraunce, L'Isle and Gough -- Exemplary Characters and Moral Lessons -- Heliodorus's Political Romance -- Homeric Beginnings -- The Insatiable Demainete -- Thyamis's Erotic Dream -- Thyamis's Priestly Family -- Rhodopis: Kalasiris's Nightmare -- Heliodorus's Cyclic Tales -- Leadership and the Law -- Thyamis Justified -- The Wanton Arsake -- The Wicked Kybele -- Recognising CharikleiaLanguage and Nationalism -- L'Isle's Political Panegyric -- Conclusion -- Part Two: Philhellene Erotic Romance -- 5 National Romance and Sidney's Arcadia -- Political Outlines -- Selective Monarchomachia -- Evolution of Arcadia -- Unfolding the Epic Cycle -- Sub-Plot and Exemplary Character -- Philisides and Tiltyard Masquing -- Costume, Device, and Narrative Strategy -- Philoclea's Bed -- Eroticising Renaissance Romance -- Erotic Romance and Erotic Sex -- Interest Theory, Philhellene Politics, and Erotic Romance -- The Novel as Theatre -- Legal and Political Process as Drama -- The End of Romance -- Conclusion -- 6 Shakespeare and Philhellene Erotic Romance Shakespeare, Amyot and North's Plutarch -- Amyot-North Diction and Style in Coriolanus (1608) -- Julius Caesar (1599), Political Identifiers and the Rhetorics of Erotic Romance -- Antony, Cleopatra, Octavius and the Huguenots -- Greville's Antony and Cleopatra: Politics and Anti-Romance -- Panegyric in Antony and Cleopatra (1606): the Rewards of Patronage -- The Winter's Tale (1609-10): Exemplary Rapprochement -- Jealousy, Tyranny, and the Aggressive 'Royal' Style -- Gendering Rhetorics: Thucydides and the Ermine -- Erotic Closure -- Cymbeline (1609-10), Rhetorical Style and the Catholic Disjunction -- Conclusion -- 7 Mary Sidney Wroth's Urania -- Philhellene Protestant Erotic Propaganda -- Disjunction at the Throne of Love -- A French Story -- The Dispossessed: Urania's Misery -- Theatres of Romance -- Interest Theory Personalised -- Techniques of Elision -- Allegorical Parallelism -- Urania as Anti-Romance -- The Great Cham and His Dynasty -- Urania as Roman à Clef -- The Metamorphosis of Mary Sidney Herbert -- Truth and Illusion -- Rodomandro's Masque -- Female Abuse and Martyrdom -- Hereditary Succession and Restoration -- Liberation, Restoration and Marital Union -- Meriana and the Macedonian Succession -- Romania Allegorised -- Closing the Sophistic Circle -- Urania as Sophistic Erotic Romance -- Conclusion -- 8 The Fate of a Genre -- The Semiotics of Erotic Romance -- Conclusion -- Bibliography -- Index of Place-Names -- General Index.
Originally published in print form: 2010.
In-house editor: Matthew Frost.
Includes bibliographical references and index.
Students and lecturers in British Renaissance literature, social & cultural history, ethics & theology.
In English.
Print version record
Keywords: Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Sidney, Philip, -- 1554-1586 -- Criticism and interpretation; Wroth, Mary, -- Lady, -- approximately 1586-approximately 1640 -- Criticism and interpretation; Wroth, Mary, -- Lady, -- approximately 1586-approximately 1640.; Sidney, Philip, -- 1554-1586.; Shakespeare, William, -- 1564-1616.; Romances, Byzantine -- History and criticism; Romances, Byzantine -- Translations into English; Romances, English -- History and criticism; Roman courtois anglais -- Histoire et critique; Literature and literary studies; Literary studies: general -- Literary studies: c. 1500 to c. 1800.; LITERARY CRITICISM -- Ancient & Classical; Romances, English; Romances, Byzantine; Biography, Literature & Literary studies -- Literature: history & criticism -- Literary studies: ancient, classical & medieval; Electronic books; Translations; Criticism, interpretation, etc